Primate lentiviral Nef proteins deregulate T-cell development by multiple mechanisms - Van Nuffel, Anouk; Ariën, Kevin K.; Stove, Veronique; Schindler, Michael; O’Neill, Eduardo; Schmökel, Jan; Van de Walle, Inge; Naessens, Evelien; Vanderstraeten, Hanne; Van Landeghem, Kathleen; Taghon, Tom; Pulkkinen, Kati; et al. (Retrovirology, 2013)
A nef gene is present in all primate lentiviral genomes and is important for high viral loads and progression to AIDS in human or experimental macaque hosts of HIV or SIV, respectively. In these hosts, infection of the thymus results in a decreased output of naive T cells that may contribute to the development of immunodeficiency. We have previously shown that HIV-1 subtype B Nef proteins can block human T-cell development. However, the underlying mechanism(s) and the conservation of this Nef function between different groups of HIV and SIV remained to be determined.